Toward a historiography of product design with an emphasis on Colombia (REVISTA NODO, 2014)
The article makes a historiographical revision of product design on three different scales: the world, Latin America and Colombia. It begins by providing a brief recollection of how the history of product design has been addressed over the years, followed by pairing up the most widespread points of view of design historians, mainly American and English, with some histories of industrial design written in Latin America and, particularly, in Colombia. It concludes that the impact of local product design in Colombian society is an issue that deserves more thorough research, to which a complete survey of companies, designers and production is essential.
Keywords: History; Industrial Design; Colombia